Functional Group Analysis of Silica Gel Based on River Sand Magnetic Mineral as Heavy Metal Absorbance - Meiliyadi, Lalu Ahmad Didik; Rahman, Muh. Zainur; Zain, Zahida Aliatu (Universitas Islam Negeri (UIN) Mataram, 2024)
Functional group analysis of silica gel synthesized from river sand magnetic minerals using the sol-gel method was conducted. River sand magnetic mineral samples were taken from Sompang River, Lombok. The synthesis method used is a sol-gel method with variation of HCl acid 10 M and NH4OH base 10 M. Morphological characterization using a Scanning Electron Microscope (SEM) and mineral content analysis using Energy Dispersive X-ray (EDX). The morphology of the resulting silica gel is granular, showing crystalline properties with a silica concentration of 77.99 ± 0.17 atomic percent. Silica functional groups before absorption showed three stretching vibrations, namely OH group stretching vibrations in Si-OH and H2O at an absorption wavelength of 3669.77 cm-1, Si-O stretching vibrations from siloxane (Si-O-Si) at an absorption wavelength of 2858.51 cm-1 and Si-O asymmetric stretching vibrations from silanol (Si-OH) at an absorption wavelength of 962.88 cm-1. While the results of the analysis of silica gel after absorption show that almost all samples have vibrational absorption in the range of 400-500 cm-1. Other vibrational absorptions in silica samples that have been used as water filters indicate that the bonding between nano-silica as an absorber and heavy metals is due to the magnetic properties of nano-silica.